A study of bacteriological profile and antibiotic sensitivity of culture proven neonatal sepsis: Neonatal Sepsis (GAIMS Journal of Medical Sciences, 2023)
Background: Neonatal sepsis is the second most common cause of neonatal mortality in India. Early detection and proper treatment of sepsis are important in reducing neonatal mortality. The emergence of antibiotic resistance among pathogens that infect newborns is of great concern. Hence, this study was done to identify the bacterial agents causing neonatal septicemia along with their antibiotic sensitivity pattern.Methods: This was a prospective study carried out at neonatal intensive care unit of a tertiary care teaching hospital of western Gujarat, India, from October 2018 to August 2020. 2739 neonates were admitted with probable sepsis during the study period. 299 neonates with positive blood cultures were recruited for the study. Antibiotic sensitivity of organisms was noted and compared with other studies.Results: Out of 299 blood culture proven sepsis, most common organism was Klebsiella pneumoniae, isolated in 98 patients (32.7%), followed by coagulase negative staphylococcus aureus in 90 patients (30.2%). Candida was the third most common organism isolated in 45 (15.1%) patients. Other bacteria isolated were Enterococcus in 33 (11.1%), Staphylococcus aureus in 17 (5.6%), Escherichia coli in 7 (2.3%), Acinetobacter spp in 6 (2%) and Pseudomonas in 3 (1%) patients. Gram positive bacteria were isolated in 140 (46.8%) patients, while, gram negative bacteria and fungus were isolated in 114 (38.2%) and 45 (15%) patients respectively. Klebsiella demonstrated maximum sensitivity to Meropenem (95%) and Piperacillin-Tazobactam (73.1%), while it showed high resistance to ampicillin (97.9%) and Cefoperazone (95.9%). Among non-beta lactam antibiotics, Klebsiella showed maximum sensitivity to colistin (100%) and Vancomycin (80%), while showed high resistance to Aminoglycosides and Quinolones. CONS showed maximum sensitivity to Cefoperazone (81.4%) and Cefotaxim (62.4%), but they showed high resistance to Ampicillin (86.5%) and Meropenem (86.9%). Among non-beta lactam antibiotics, CONS showed maximum sensitivity to Linezolid (100%) and Vancomycin (98%), while showed high resistance to Aminoglycosides and Quinolones.Conclusions: The most common organism isolated was Klebsiella and it showed high resistance to 1st, 2nd and 3rd line antibiotics (Ampicillin, Aminoglycosides, Cefoperazone and Quinolones). Due to the emergence of antibiotic resistance in NICU, it is important to know antibiotics sensitivity and resistant pattern of various organisms for neonatal sepsis.